Art therapy and neuroscience: evidence, limits, and myths - Strang, Christianne E. (Frontiers in Psychology, 2024)
The evidence base for the effectiveness of art therapy continues to grow, even as a mechanistic understanding of how art therapy works remains limited. One promising avenue for increasing our understanding of how and why art therapy works is through the lens of neuroscience. A neuroscience-based approach to art therapy provides opportunities for improving understanding of the neural processes that underlie the complex interaction between perception, cognition, emotion and behavior that play out in the art therapy process. Understanding how therapeutic change occurs can result in improved treatment and better outcomes for clients. However, it can be tricky to connect art therapy and psychological theory directly to neural responses. The purposes of this perspective are to provide an overview of the current evidence and limits of neurobiological concepts of neuroplasticity, mirror systems, and interoception as applied to art therapy practice, and to provide updated information about outdated concepts that are still actively used in clinical practice. Critical analysis and understanding of the current scientific knowledge base can then be used to guide art therapy practice and support the development of hypothesis-based research to determine the primary mechanisms that drive the observed effects of art therapy interventions.